Ob Osobennostâh stilističeskih ošibok v rerajterskih novostnyh internet-soobŝeniâh (na promere matarialov agentstv NEWSru.com i Lenta.ru) - Laŝuk, Ol’ga R. (Stylistyka, 2019)
The author researches the field of production the news messages on the Internet by rewriting, the specifics of this field, conditioned both by the method of production of the information item and by the consumers’ requirements. The author investigates the stylistic mistakes in news stories produced by agencies that specialize in rewriting.